Data for: A longitudinal study of the dynamics of Mycoplasma bovis antibody status in primiparous cows and bulk tank milk in Swedish dairy herds - Hurri, Emma; Tråvén, Madeleine (Swedish University of Agricultural Sciences, 2024)
In this study the aims were: (1) to monitor the changes in M. bovis antibody status in BTM and milk from PP cows in Swedish dairy herds over time, and (2) to investigate potential risk factors and herd health variables associated with M. bovis antibodies in primiparous cows.

Study population
Five regions in the south of Sweden with previously knowned cases of M. bovis were selected for the study. Dairy herds from these regions with an average of more than 70 cows (both lactating and dry) on a yearly basis and affiliated to the Dairy Herd Improvement (DHI) database (Växa Sverige) were invited to participate in the study. 139 herds accepted and ten herds joined later due to contact with infected herds or diagnosing Mycoplasma bovis at the herd. In total, 143 herds were used in the statistical analysis, six herds had no samples from primiparous cows and were dropped.

Sampling
Herds were sampled four times with approximately six-month intervals, in (1) September 2019, (2) February 2020, (3) November 2020 and (4) May 2021, with a two-month long sampling window each time. For each herd, on each sampling occasion, milk samples were collected from the three youngest home-bred PP cows and BTM.

Data
Herd-level data on health and production variables were retrieved from the Dairy Herd Improvement database, Växa Sverige. The data were aggregated in four 12-month periods calculated backwards from the start of each sampling period, (1) 2019-09-01, (2) 2020-02-01, (3) 2020-11-01 and (4) 2021-05-01. Data regarding mortality, culling rates, reproductive performance, and veterinary-reported clinical diseases were calculated as cases per 100 animals at risk. Breed was classified into four categories on herd level, the main breed constituting more than 80% of the cows. Herd-level data in 12-month periods regarding herd size (i.e., number of female animals >24 months old), number of introduced cattle, median age of introduced cattle, and number of herds the introduced cattle were received from (inherds) were collected from the National Cattle Database (Swedish Board of Agriculture 2022). Data on herd size (number of milking cows) in fifteen herds not affiliated with the DHI were retrieved from a questionnaire answered by these farmers during autumn 2020.

Provtagning och datauttag om produktion och hälsa för 143 mjölkgårdar i södra Sverige. Prover insamlades under två år och data har tagits ut för 3 år. Proverna är tankmjölksprov och mjölkprov från förstakalvare och de har analyserats för Mycoplasma bovis antikroppar. Provtagningsresultat och variabler om hälsa, produktion, besättningsstorlek, ras samt inköp av djur på gårdsnivå inklusive förklaringar till dessa variabler.

För en mer fullständig beskrivning hänvisas till den engelska beskrivningen.
Data för: A longitudinal study of the dynamics of Mycoplasma bovis antibody status in primiparous cows and bulk tank milk in Swedish dairy herds
Keywords: Mycoplasma bovis; Mycoplasma bovis; Biosecurity; Bioskydd; heifers; mycoplasmoses; Mycoplasmopsis bovis; Mycoplasmopsis bovis; primiparous cow; förstakalvare; Plants and animals; Växter och djur; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Veterinary Science; Veterinärmedicin; Other Veterinary Science; Annan veterinärmedicin